Escaping the resource curse in regional development: a case study on the allocation of oil royalties. (1st January 2015) - Rocchi, Benedetto; Landi, Chiara; Stefani, Gianluca; Romano, Severino; Cozzi, Mario
The aim of this paper is to evaluate the socio–economic impact of the allocation of royalties from oil extraction on regional development through a case study on the Basilicata region (Italy). We examine how the regional government's chosen policies have impacted the income of Basilicata residents and the economic development of the region and how a different set of choices may reveal a more effective approach to turning revenue into long–term public benefits. The analysis focuses on growth as well as on distributive impacts of the allocation of royalties. The results clearly show that the past allocation of the royalties accruing to regional government into regional policies generated little impact in terms of economic growth and occupation, the total well below what was expected. Appreciable impacts on incomes and occupation will not be forthcoming unless resources are redirected towards supporting a stronger competitiveness of the regional economic system.